PERAN DPRD DALAM PEMBENTUKAN RANCANGAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN DEMAK - Aini, Putri Diyan Nur; Nuswanto, A. Heru; Junaidi, Muhammad; Suwandi, Dedi (Fakultas Hukum, Universitas Semarang, 2024)
This research aims to determine the role of the DPRD in forming regional revenue and expenditure budget planning in Demak Regency. The DPRD discussed the posture and structure of the APBD budget with TAPD through budget body meetings to check the suitability of the RPJMD and Demak Regency development policies through commission meetings in accordance with their duties and authority. By using a problem formulation, namely regarding, what is the role of the DPRD in forming the APBD draft in Demak Regency, and what factors become obstacles forming the APBD draft in Demak Regency and how to resolve them. The research objectives include, to find out the role of the DPRD in forming the APBD draft in Demak Regency, and to find out the factors that become obstacles in the development of the APBD draft in Demak Regency and how to resolve them. Research specifications use descriptive analytical research, namely research that describes a condition or situation. Based on the results of research on the Role of the DPRD in Forming APBD Drafts in Demak Regency, the DPRD discussed the posture or structure of the APBD budget with TAPD through budget body meetings to check the RPJMD and development policies in Demak Regency in accordance with their duties and authority, which became the reference, namely Permendagri Number 15 of 2023 concerning Guidelines for Preparing the APBD for Fiscal Year 2024, and discusses the obstacle factors in conflicting APBD designs in Demak Regency and how to resolve them. According to Law. no. 17 of 2014 concerning the MPR, DPR, DPD and DPRD, it is hoped that it can improve the performance of each representative institution in carrying out its functional duties based on the principle of mutual checks and balances, as well as creating a democratic, effective and accountable people's representative institution. AbstrakPenelitian ini bertujuan untuk mengetahui Peran DPRD Dalam Pembentukan Rancanngan Anggaran Pendapatan Dan Belanja Daerah (APBD) Di Kabupaten Demak. DPRD membahas mengenai postur dan struktur anggaran APBD bersama TAPD melalui rapat badan anggaran untuk mengecek kesesuaian RPJMD dan kebijakan pembangunan Kabupaten Demak melalui rapat komisi sesuai tugas dan kewenangannya. Permasalahan dalam penelitian ini difokuskan pada peran DPRD dalam pembentukan rancangan APBD di Kabupaten Demak, kendala dan cara menyelesaikannya. Tujuan penelitian yaitu, untuk mengetahui peran DPRD dalam pembentukan rancangan APBD di Kabupaten Demak, dan untuk mengetahui faktor yang menjadi kendala dalam pembenturan rancangan APBD di Kabupaten demak dan cara menyelesaikannya. Spesifikasi penelitian menggunakan deskriptif analitis yaitu penelitian yang menggambarkan suatu kondisi atau keadaan. Sampel dalam penelitian ini menggunakan metode purposive sampling. Berdasarkan hasil penelitian Peran DPRD dalam Pembentukan Rancangan APBD di Kabupaten Demak, DPRD membahas mengenai tentang postur atau struktur anggaran APBD bersama TAPD melalui rapat badan anggaran untuk mengecek RPJMD dan kebijakan pembangunan di kabupaten demak melalui kesesuaian dengan tugas dan kewenangannya, acuannya yaitu permendagri Nomor 15 Tahun 2023 tentang Pedoman Penyusunan APBD Tahun Anggaran 2024, dan membahas mengenai faktor kendala dalam pembenturan rancangan APBD di Kabupaten demak dan cara menyelesaikannya. Menurut UU No. 17 tahun 2014 tentang MPR, DPR, DPD, dan DPRD, diharapkan dapat meningkatkan kinerja masing- masing lembaga perwakilan dalam melaksanakan tugas fungsinya berdasarkan check and balances.